1986
DOI: 10.1007/bf01655319
|View full text |Cite
|
Sign up to set email alerts
|

Volvulus of the small intestine in adults

Abstract: The presentation and subsequent management of 53 patients with volvulus of the small bowel are reviewed. Important features of the presentation are the acute onset of the abdominal pain and its severity which is often inconsistent with the findings on clinical examination. The diagnosis was made preoperatively from plain abdominal x-rays in only 1 patient, although several radiological features are described. In 16 patients there were no obvious predisposing factors, although in the remaining 37 patients the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
4

Year Published

1993
1993
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 7 publications
(4 reference statements)
2
37
0
4
Order By: Relevance
“…[1][2][3] Midgut volvulus can be primary, without finding any associated underlying cause, or secondary to other congenital or acquired conditions. It is frequent in geographical areas, such as Middle East, Asia, and Central Africa, related to factors such as lower socioeconomic status, fiber consumption after prolonged fasting (Muslims during the Ramadan), parasitic infections and diabetic autonomous neuropathy, while it has a low incidence in Western countries.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Midgut volvulus can be primary, without finding any associated underlying cause, or secondary to other congenital or acquired conditions. It is frequent in geographical areas, such as Middle East, Asia, and Central Africa, related to factors such as lower socioeconomic status, fiber consumption after prolonged fasting (Muslims during the Ramadan), parasitic infections and diabetic autonomous neuropathy, while it has a low incidence in Western countries.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,4 However, no particular dietary factors were pointed out in other reports. 13,14 Nomura et al 13 suggested that the large volume of air in the intestine and the strong peristalsis resulting from frequent swallowing of air may be an etiologic factor. Another author noted that with the abrupt transit of a bulky semisolid meal into the proximal jejunum, there was a natural migration of this heavier segment of intestine into the left lower quadrant, which forces the distal empty loops into a clockwise rotation into the right upper quadrant.…”
Section: Discussionmentioning
confidence: 99%
“…Another author noted that with the abrupt transit of a bulky semisolid meal into the proximal jejunum, there was a natural migration of this heavier segment of intestine into the left lower quadrant, which forces the distal empty loops into a clockwise rotation into the right upper quadrant. 14 The preoperative diagnosis of primary small bowel volvulus is rather difficult. Plain abdominal films, CT scans, barium swallows, and angiography are usually used for the preoperative diagnosis of this condition.…”
Section: Discussionmentioning
confidence: 99%
“…If used, angiography can exhibit spiralling, twisted arterial branches originating off the superior mesenteric artery producing the characteristic 'barber pole' sign [11]. SBV has an overall mortality of 10%-47% [12], but a significantly higher mortality in patients with gangrenous bowel (20%-100%) [11].…”
Section: Discussionmentioning
confidence: 99%